2013
DOI: 10.1186/1471-2458-13-341
|View full text |Cite
|
Sign up to set email alerts
|

Effects of secondhand smoke on the birth weight of term infants and the demographic profile of Saudi exposed women

Abstract: BackgroundMaternal exposure to tobacco smoke during pregnancy is associated with detrimental effects on the mother and the fetus including; impaired fetal growth, low birth weight and preterm delivery. In utero exposure to tobacco is implicated in the etiology of many adults’ diseases including obesity, diabetes and hypertension.The objectives of this study were to evaluate the effects of Secondhand Tobacco Smoke (SHS) exposure on newborns’ anthropometric measurements and to compare the demographic profile of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
43
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 28 publications
13
43
2
2
Order By: Relevance
“…This can be due to either the participants and the active smokers have good knowledge about the harms of SHS exposure and they follow measures to avoid it or it could be due to under reporting by the participants of the real timing of exposure. Significant association between the low level of education of the pregnant women in the study and the more exposure to SHS is found in this study, which has been showed in the literature (3). Being an unemployed is significantly associated with more exposure to SHS among the participants and this could be due to the less chance to be an employed with low level of education which takes us back to the point of the low level of education is associated with more exposure or it could be due to that the unemployed participants stay at home for longer time which increases the risk of more exposure.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This can be due to either the participants and the active smokers have good knowledge about the harms of SHS exposure and they follow measures to avoid it or it could be due to under reporting by the participants of the real timing of exposure. Significant association between the low level of education of the pregnant women in the study and the more exposure to SHS is found in this study, which has been showed in the literature (3). Being an unemployed is significantly associated with more exposure to SHS among the participants and this could be due to the less chance to be an employed with low level of education which takes us back to the point of the low level of education is associated with more exposure or it could be due to that the unemployed participants stay at home for longer time which increases the risk of more exposure.…”
Section: Discussionsupporting
confidence: 79%
“…It is being thought that severe military conflicts in Africa shorten the expected lifetime for more than 2 years. In general, WHO had calculated that 269 thousand people had died in 1999 due to the effect of wars and that loss of 8.44 million healthy years of life had occurred (2,3). Wars negatively affect the provision of health services.…”
Section: War and Women's Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…SHS ϭ second hand smoke LBW ϭ low birthweight NR ϭ not reported pregnancy, 5,6 to quantity of exposure to SHS, 11,13,[24][25][26][27][28][29][30][31][32][33]35,36 and to cotinine level (Tables 1 and 2). 12,14,17,22,37 One study 10 confirmed that exposure to SHS during pregnancy was a cause of LBW and not merely an association.…”
Section: Exposure To Secondhand Smoke During Pregnancy and Lbwmentioning
confidence: 99%
“…A cross-sectional study, 36 based on self-reports from 3,424 nonsmoking pregnant women (including 1,085 exposed to SHS during pregnancy and 2,341 unexposed), found that mean birthweight of babies born to exposed mothers was 35 g less than that of babies born to unexposed mothers. A case-control study 35 based on self-reports from 1,761 nonsmoking women who delivered a baby reported that, compared with unexposed mothers, mothers exposed to SHS in homes without a window had higher risk (odds ratio, 1.36; although 95% CI values included the null) of having LBW babies, whereas exposed mothers living in homes with window ventilation had no increased risk.…”
Section: Findings From More Recent Studies Of Exposure To Secondhand mentioning
confidence: 99%